Rural Status of Equine Assisted Activities and Therapies and Cancer Survivors - Khalid Bandar Almasloukh; Pamela Stewart Fahs (Rural Nurse Organization; Binghamton University, 2020)
Background: Although equine assisted activities and therapies (EAAT) are rapidly increasing, as are cancer survival rates, little is known about the engagement of cancer survivors in EAAT. One may conceptualize equine or horse related activities as occurring in rural areas; however, the rural status of EAAT centers are not fully reported. Purpose: To explore the rural status of EAAT centers, and whether EAAT is provided for cancer survivors and the more common service for post-traumatic stress disorder at those centers. Method: A quantitative descriptive analysis was conducted of publicly available data after an exempt status decision of an Institutional Review Board. Services using EAAT for those with terminal illnesses, post-traumatic stress disorder and cancer survivors were examined. Rural status was evaluated for all organizational members (N = 784) of Professional Association of Therapeutic Horsemanship International (PATH Intl.). Roy adaptation model was used as a theoretical framework in this project. Findings: All types of the organizational members, cluster in urban areas more than rural areas. Significant relationship (p = 0.039) was found between rural status and type of membership, where more urban than rural centers were premier accredited center members. Most of the contacted and responding centers stated that they do provided EAAT for cancer survivors (n = 204); however, only (n = 26) centers have programs specifically designed for cancer survivors. Conclusion: There are not only less EAAT rural than urban centers, but rural centers also tend to have lower quality level membership based on PATH Intl. standards. Although EAAT is provided for cancer survivors, identifying effective ways to provide EAAT and standardization of programs for cancer survivors is recommended. DOI: http://doi.org/10.14574/ojrnhc.v20i2.601